Andagtslitteraturen i 1700-tallet og dens anvendelse i 1800-tallet - Rasmussen, Jens (Kirkehistoriske Samlinger, 2025)
The principal source of this article is Frederik Boye’s Nogle faa udvalgte og med Blod besprængte Blomster from 1750. As seen in this small devotional book, the tradition of Herrnhutism has manifested itself in various reprinted editions from 1750 to 1925. This points to continuity in circulation during the 19th century. Together with other devotional literature mentioned in this article Boye’s devotional book express common Lutheran foundation. Devotional revivalists expanding during the 19th century read devotional books from the 17th and 18th centuries ensuring continuity. It points to the fact that revivalists were faithful to the old world-view and Absolutism’s uniformity principle. This kind of national culture goes back to Lutheranism and Reformation because the revivalists used Luther’s sermons. So, a solid foundation for the revivalists’ attitudes is based upon their reading of devotional literature and Martin Luther’s writings. Devotional literature belongs to a tradition of orthodox and pious writings. This is the kind of literature that affects the religious revivalists. It is read by the leaders who pass their message on to religious assemblies. In accordance with laymen’s responsibility to interpret the Gospel, the revivalists communicate the Scripture and share devotional literature in religious assemblies which develop and expand in various places on the island of Funen around 1820. Soon after, the laymen’s movement reaches Jutland and Zealand including Copenhagen. The two religious branches called Grundtvigianism and The evangelical wing of the Church of Denmark (Indre Mission) both have their roots in the early 1820 revivalist movements, which include Herrnhutism. The characteristic Danish layman influence should be taken into consideration when trying to understand the present Danish National Church in terms of cultural identity and independence.